RESEPSI GAUDIUM ET SPES OLEH GEREJA INDONESIA - Laurentius Sutadi (P3TK, Sanata Dharma University, 2013)
The 50th anniversary of The Second Vatican Council opening is an important moment to research the Catolic followers reception of Church teaching in The Second Vatican Councils documents. Focus of this research is the Church reception for Pastoral Constitution of Gaudium et Spes. The pastoral Constitution on the Church in the Modern World Gaudium et Spes is the longest and the most complex document produced by the Second Vatican Council. This document articulates the relationship between the church and the world. The Church reception for Gaudium et Spes can be detected from three points: the Church effort to teach, the Church understanding to this substance document, and various Church movement that implement Gaudium et Spes items teaching at the centre world.